2020
DOI: 10.9734/jerr/2020/v10i317038
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Tomato Water Productivity Using Aquacrop Model in Njoro Sub County, Nakuru, Kenya

Abstract: Aims: To model tomato water productivity under deficit sub – surface drip irrigation and grass mulch densities using Aquacrop model. Study Design: The study was factorial experimental with twelve treatments. Place and Duration of Study: Tatton Agriculture Park, Egerton University, Nakuru, Kenya between January to May 2019. Methodology: Tomato (Lycopersicon esculentum mill) crop (Tylka F1) was used to determine the effect of deficit irrigation and mulching on its productivity. Aquacrop model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…These results are in agreement with the findings of [49] who reported that the highest growth components of onions were recorded from full irrigation, and the lowest heights were recorded from high-stressed treatment. The current result was also in line with [59] who stated that 100%ETc resulted in the highest values of growth parameters, while 50%ETc led to the lowest, with intermediate values recorded at 75%ETc. [60] also reported the lowest plant heights obtained from treatments receiving a low amount of water of 50%ETc.…”
Section: Components Of Onionsupporting
confidence: 92%
“…These results are in agreement with the findings of [49] who reported that the highest growth components of onions were recorded from full irrigation, and the lowest heights were recorded from high-stressed treatment. The current result was also in line with [59] who stated that 100%ETc resulted in the highest values of growth parameters, while 50%ETc led to the lowest, with intermediate values recorded at 75%ETc. [60] also reported the lowest plant heights obtained from treatments receiving a low amount of water of 50%ETc.…”
Section: Components Of Onionsupporting
confidence: 92%
“…However, when the SSI irrigation technique was combined with BPE soil mulch under the DI regime, it was found to be the most effective in conserving irrigation water. This combination not only mitigated the negative effects of the DI regime but also promoted plant health and improved water productivity (Abdelhady et al, 2017;Chen et al, 2018;Abd El-Wahed et al, 2020;Sang et al, 2020).…”
Section: Effect Of Irrigation Scheduling Irrigation Technique and Soi...mentioning
confidence: 99%
“…Mulching soil with either organic materials or black polyethylene sheets, even though the black polyethylene sheets are more effective than organic materials, reduces evaporation, retains soil moisture, decreases the effect of ambient temperature on soil temperature, and suppresses weed growth. These all can support better vegetative growth and overall plant health (Abdelhady et al, 2017;Chen et al, 2018;Abd El-Wahed et al, 2020;Sang et al, 2020).…”
Section: Tomato Plants' Vegetative Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice has been carried out in different climatic and agronomic conditions on the yield and productivity of different crops in different areas, such as potato [15,17,18], maize [19,20], cassava [21], chickpea [22], canola [23], and tomato [24,25,26,27,28]. However, most of these studies have investigated the applicability of the AquaCrop model under reduced water application of independent of growth stages and also the model performance varied with variations of crop types, climate, locations, irrigation seasons [29], the soil texture affects the model performance [30], some reports were found in the literature concerning the calibration of this model for arid climates on tomato crop.…”
Section: Introductionmentioning
confidence: 99%